A multiple objective tabu search approach for end-of-life product disassembly. (4th January 2010) - Kongar, Elif; Gupta, Surendra M.
This paper addresses the disassembly-to-order (DTO) and the disassembly sequence planning (DSP) problems and employs a multiple objective tabu search (MOTS) algorithm to solve them. The focus of the study is on the disassembly operations of end-of-life (EOL) products taken back from their last users (owners). The proposed approach aims at disassembling the EOL products for reusing, recycling, storing and properly disposing them in an environmentally benign manner. Thus, the model controls and restricts the environmental damage while increasing the value captured from the EOL products. These goals are achieved in an economically viable manner. The proposed model employs two independent modules, namely, the DTO module and the DSP module. The DTO module embodies multiple objectives and provides various options for the number of items to be disassembled from each EOL product for resale, recycling, storage and proper disposal, along with the numbers and types of EOL products to be taken back. The module considers both environmental and financial objectives while meeting the demand expectations. The DSP module provides multiple feasible disassembly sequences for the EOL products. The module considers and preserves the precedence relationships among the items while fulfilling multiple objectives.